Liver ergothioneine accumulation in a guinea pig model of non-alcoholic fatty liver disease. A possible mechanism of defence?. (2nd January 2016) - Cheah, Irwin K.; Tang, Richard; Ye, Peng; Yew, Terry S. Z.; Lim, Keith H. C.; Halliwell, Barry
ABSTRACT: L-ergothioneine (ET), a putative antioxidant compound acquired by animals through dietary sources, has been suggested to accumulate in certain cells and tissues in the body that are predisposed to high oxidative stress. In the present study, we identified an elevation of ET in the liver of a guinea pig model of non-alcoholic fatty liver disease (NAFLD), elucidated a possible mechanism for the increased uptake and investigated the possible role for this accumulation. This increase in liver ET levels correlated with cholesterol accumulation and disease severity. We identified an increase in the transcriptional factor, RUNX1, which has been shown to upregulate the expression of the ET-specific transporter OCTN1, and could consequently lead to the observable elevation in ET. An increase was also seen in heat shock protein 70 (HSP70) which seemingly corresponds to ET elevation. No significant increase was observed in oxidative damage markers, F2 -isoprostanes, and protein carbonyls, which could possibly be attributed to the increase in liver ET through direct antioxidant action, induction of HSP70, or by chelation of Fe 2+, preventing redox chemistry. The data suggest a novel mechanism by which the guinea pig fatty liver accumulates ET via upregulation of its transporter, as a possible stress response by the damaged liver to further suppress oxidative damage and delay tissue injury. Similar events may happen in other animal models of disease, and researchers should be aware of the possibility.